Pemberdayaan Petani Buah Naga Desa Nusa Makmur Kecamatan Air Kumbang Kabupaten Banyuasin - Wulansari , Febrisa; Suryati, Suryati; Muzaiyanah, Muzaiyanah (CV. ITTC INDONESIA, 2023)
This thesis is entitled